Measure of personal stigma and perceived stigma: An exploratory factor analysis - Ines, Jennifer V. (Animo Repository, 2019)
The role of stigma in people’s decision to seek help for mental health concerns had been argued due to conflicting research findings. To date, there are few instruments that assess mental health stigma. The present study aimed to examine the validity and develop a modified version of the Depression Stigma Scale to check if it is a valid instrument in assessing Filipino college students’ mental health stigma and know the underlying dimensions of mental health stigma among Filipino college students. To fit the requirements needed, the Depression Stigma Scale which originally had 16 items is reduced to 14 items since they are not applicable to college students. The instrument is administered to 1077 Filipino college students (N=1077) who participated in the online survey. Only a total of 797 (74%) participants qualified in the study satisfying the requirements including personal and parental consent, 367 were male (46%) and 430 (54%) were female with ages ranged from 15 to 21, mean age of 16.57 and SD 0.78. Result of Exploratory Factor Analysis (EFA) of the 14-item scale confirms that mental health stigma among Filipino college students includes 2 factor solutions for the personal stigma scale (Weak-not-sick; and Dangerous/undesirable) and supports findings from previous studies that there are 2 dimensions under personal stigma. However, Perceived stigma scale is a unitary dimension in the current study and differs from the result of previous studies conducted. Implication, limitations and recommendation for future researches are discussed.